2021
DOI: 10.1155/2021/2131405
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Standardized Nursing Intervention Combined with Mindfulness Stress Reduction Training on the Curative Effect, Negative Emotion, and Quality of Life in Patients with Chronic Gastritis and Gastric Ulcer

Abstract: Objective. To explore the curative effect of standardized nursing intervention combined with mindfulness stress reduction training in patients with chronic gastritis and gastric ulcer and its influence on negative emotion and quality of life. Methods. Total of 146 patients with chronic gastritis and gastric ulcer admitted to our hospital from August 2018 to February 2020 were collected and divided into the control group (n = 73) and study group (n = 73) according to patients’ wishes and the random number metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The average symptom score was 4.2, indicating that participants with CG had at least two symptoms on average. The average age of participants was 39.1, which corresponded to the general trend of CG patients being younger (18). Additionally, due to the proximity of our hospital to the university, a relatively large number of undergraduate and postgraduate students (26.1%) participated in the survey.…”
Section: Discussionmentioning
confidence: 99%
“…The average symptom score was 4.2, indicating that participants with CG had at least two symptoms on average. The average age of participants was 39.1, which corresponded to the general trend of CG patients being younger (18). Additionally, due to the proximity of our hospital to the university, a relatively large number of undergraduate and postgraduate students (26.1%) participated in the survey.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to be comprehensive. In clinical practice, nursing intervention is a commonly used method, which can provide patients with better and comprehensive nursing services [7]. Preoperative intervention can make good preoperative preparations to effectively prevent the occurrence of postoperative emergencies, and ensure patients to receive treatment in the best state.…”
Section: Discussionmentioning
confidence: 99%
“…The National Institute of Mental Health showed that the prevalence of mental disorders in patients with somatic diseases is as high as 41%[ 17 ]. Therefore, while paying clinical attention to the diagnosis and treatment of physical diseases, we should also pay attention to mental and psychological interventions, as the number of patients with GU complicated with depression in China has increased annually[ 18 ]. Several factors affect the pathogenesis of GU, which is complicated with depression.…”
Section: Discussionmentioning
confidence: 99%